Role of Testing Conditions in Formation of Tribological Layers at Line Contacts of Antifriction CF-Reinforced PI- and PEI-Based Composites; Molecules; Vol. 27, iss. 19 - Panin A. V. Alexey Viktorovich; Luo Jiangkun; Buslovich D. G. Dmitry Gennadjevich; Alekseenko V. O. Vladislav Olegovich; Kornienko L. A. Lyudmila Aleksandrovna; Byakov A. V. Anton Viktorovich; Paymushin V. N. Vitaly Nikolaevich; Shugurov A. R. Artur Rubinovich (2022, 2022)
Title screen